Burns Anxiety Inventory Factor Model: Validation in a College Student Population - Moerdiono Ramadhana Reksoprodjo; Andri Setia Dharma (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2026)
Anxiety is one of the most common psychological disorders experienced by university students across the world. However, many cases of anxiety remain unidentified despite individuals exhibiting clinical symptoms. One of the instruments used to measure anxiety is the Burns Anxiety Inventory (BAI). Nevertheless, studies on the validity of this instrument in the Indonesian context are still limited. This study aims to evaluate the factor structure of the BAI. The research focused on examining the factor structure of the BAI (33 items) using a Confirmatory Factor Analysis (CFA) approach and testing its validity through distinct group evidence. The sample consisted of active university students aged 18–25 in the Greater Jakarta (Jabodetabek) area, with a total of 400 participants. CFA results of the BAI indicated that the three-factor model demonstrated an acceptable fit to the data and was empirically justifiable. Additionally, distinct group validity was supported by findings showing that female participants reported significantly higher levels of anxiety than male participants, consistent with previous empirical studies. These findings indicate that the BAI are valid and reliable instruments for measuring anxiety among Indonesian university students.